The Influence of Halal `Labels, Promotion, Service Quality, Brand Image, and Price on Consumer Decisions in Buying Medicines at the Pharmacy in Jember Regency - Suayroh Tri Damayanti (Sekolah Tinggi Ilmu Bahasa Arab Darul Ulum Banyuanyar Pamekasan, 2023)
In product marketing in Indonesia, halal is a fundamental matter, especially regarding food; this has been proven by previous research, while research on marketing drugs related to halal has yet to be found by researchers in previous studies. Given the circulation of drugs containing pig DNA, labels should be an essential thing to consider in every consumer purchasing decision because medicines are the same as a food whose use is consumed directly by the body. This study aims to analyze the effect of halal labels, promotions, service quality, brand image, and prices on consumer decisions in buying medicines at pharmacies in the Jember Regency. This type of research is associative research with a quantitative approach. The population of this study is consumers who buy drugs at pharmacies in the Jember district, which fall into the unlimited population category(infinite). The sampling technique uses the technique of nonprobability sampling with the approach of purposive sampling. Data collection using observation (observation), questionnaire (questionnaire) and literature study. This study uses multiple linear regression analysis. The data were tested using the classical assumption, Multicollinearity, Heteroscedasticity and Normality tests. The hypothesis test uses a partial test (t-test) and a simultaneous test (f-test). Use the coefficient of determination test (R2) to measure how far the model can explain the dependent variable's variation. The results of this study show that based on the significance value (Sig) on the halal label, the probability value is > α which is 0.326 > 0.05, so there is no significant effect between the halal label on consumer decisions on promotions and the probability value is > α which is 0.886 > 0.05. There is no significant effect between promotion on consumer decisions on service quality. The probability value is > α which is 0.002 <0.05, so there is a significant influence between service quality on consumer decisions; for the on-brand image, the probability value is > α which is 0.000 <0.05, then there is a significant influence between the brand image on consumer decisions, and at prices, the probability value > α is 0.128 > 0.05, so there is no significant effect between prices on consumer decisions in buying medicines at pharmacies in Jember district.